A Comparative Study of Whole Body Vibration Training and Pelvic Floor Muscle Training on Women's Stress Urinary Incontinence: Three- Month Follow- Up - Azizeh Farzinmehr; Azar Moezy; Jalil Koohpayehzadeh; Maryam Kashanian (Tehran University of Medical Sciences, 2016)
Objective: To determine whether Whole Body Vibration Training (WBVT) is effective at improving pelvic floor muscles strength in women with Stress Urinary Incontinence (SUI). Materials and methods: The study was designed as a randomized clinical trial. 43 women with SUI were randomly assigned in two groups; WBVT and Pelvic Floor Muscle Training (PFMT) and received interventions for four weeks. Pelvic floor muscle (PFM) strength, quality of life and incontinence intensity were evaluated. All measurements were conducted pre and post intervention and also after 3 months in all participants. The ANOVA and the independent sample t test were applied respectively to determine the differences in each group and between the groups. Results: This study showed the WBVT protocol in this study was effective in pelvic floor muscles strength similar to PFMT, and also in reducing the severity of incontinence and increasing I-QOL questionnaire score. We found significant differences in each group pre and post intervention (p = 0.0001); but no significant difference in comparison of two groups' outcomes. Also after three-month follow up, there was no significant difference between groups. Conclusion: The findings of this study showed the beneficial effects of WBVT in improving pelvic floor muscles strength and quality of life in patients with urinary incontinence in four-week treatment period and after three months follow up.